2005
DOI: 10.1021/ja055099u
|View full text |Cite
|
Sign up to set email alerts
|

The Ferrous Verdoheme−Heme Oxygenase Complex is Six-Coordinate and Low-Spin

Abstract: A biosynthetic and enzymatic method was developed for the preparation of 13C-labeled verdoheme, which permits the 13C NMR spectroscopic characterization of this elusive intermediate in the heme oxidation path catalyzed by the enzyme heme oxygenase. The 13C NMR data indicate that the ferrous verdoheme complex of Neisseria meningitides heme oxygenase is hexacoordinate and diamagnetic, with a proximal histidine and likely a distal hydroxide as axial ligands. The coordination number and spin state of the ferrous v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…Addition of pyridine to the reaction mixture, results in a well defined peak in the visible region at 630 nm, similar to that of the Fe III -verdoheme-pyridine complex [15]. This observation was further confirmed by ESI-MS analyses of the reaction extract which had similar mass fragmentation pattern observed for an authentic verdoheme sample, suggesting that the trapped intermediate is indeed Fe III -verdoheme (Fig.…”
Section: Reaction Of the Heme-pa-ho Complex With Ascorbic Acid And Itsupporting
confidence: 65%
See 1 more Smart Citation
“…Addition of pyridine to the reaction mixture, results in a well defined peak in the visible region at 630 nm, similar to that of the Fe III -verdoheme-pyridine complex [15]. This observation was further confirmed by ESI-MS analyses of the reaction extract which had similar mass fragmentation pattern observed for an authentic verdoheme sample, suggesting that the trapped intermediate is indeed Fe III -verdoheme (Fig.…”
Section: Reaction Of the Heme-pa-ho Complex With Ascorbic Acid And Itsupporting
confidence: 65%
“…Peaks were identified based on MS of authentic sample of heme, verdoheme, and Fe III -biliverdin. Fe III -verdoheme was prepared as previously described [15].…”
Section: Hplc and Esi-ms Analysis Of The Heme-pa-ho Reaction Productsmentioning
confidence: 99%
“…7A, B). The existence of hexacoordinated low-spin Fe(II)-verdoheme with either water or hydroxide as the sixth verdoheme iron ligand had been proposed by previous spectroscopic studies [62,63], but the verdoheme-hHO-1 structure did not show the sixth ligand (Fig. 7A).…”
Section: Structural Studies Of the Verdoheme-ho Complexmentioning
confidence: 55%
“…Resonance Raman [27] and 13 C-NMR [28] studies suggested the presence of a distal water molecule. Also, in our crystal structure of ferrous verdoheme-rHO-1 complex, a water molecule was observed as the distal ligand [29], but a water molecule was not seen in the crystal structure of ferrous verdoheme-human HO-1 complex [20].…”
Section: Introductionmentioning
confidence: 98%